2014
DOI: 10.1093/cercor/bhu101
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal Cortex Reactivity to Angry Facial Expression in a Social Interaction Correlates with Aggressive Behavior

Abstract: Altered neural processing of social signals such as angry facial expressions has been associated with increased aggressive behavior, but evidence for this relationship in healthy persons using ecologically valid experimental designs is lacking. We presented socially relevant videos of facial expressions in a functional magnetic resonance imaging (fMRI) version of the well-established Taylor Aggression Paradigm and investigated 41 healthy male participants, of whom 32 were included in the analysis. In each roun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
79
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 35 publications
17
79
2
2
Order By: Relevance
“…The amygdala shares extensive reciprocal connections with the OFC, damage to which has also been associated with social deficits (Beer et al, 2006). The OFC is involved in social and antisocial behavior (Passamonti et al, 2010), self-monitoring (Beer et al, 2006), and social adaptation (Beyer et al, 2014). However, imaging studies of the OFC in NF1 are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…The amygdala shares extensive reciprocal connections with the OFC, damage to which has also been associated with social deficits (Beer et al, 2006). The OFC is involved in social and antisocial behavior (Passamonti et al, 2010), self-monitoring (Beer et al, 2006), and social adaptation (Beyer et al, 2014). However, imaging studies of the OFC in NF1 are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Both the sham rats and the ACC‐lesioned rats were happy to socialize with, or to confront other same sex stranger rats in nonforaging contexts. Social interactions and social agonistic behaviors were not affected by ACC lesions, which was inconsistent with the study by Peter H. Rudebeck, whose results showed ACC lesions affected the utilization of social information, diminished social behavior, and reduced social stimulating memory, whereas normal rats habituated to socialize with other rats (Rudebeck et al., 2007), as well as another recent study reported that activity in the ACC was positively related to response to aggressive behavior (Beyer, Munte, Gottlich, & Kramer, 2015). These inconsistent results were probably due to the different procedures used to assess social interaction behavior as well as variability in lesion locations.…”
Section: Discussionmentioning
confidence: 82%
“…Eight out of 28 contrasts contributed to the cluster in vmPFC (MDE 5 21.26%; 2MDE 5 35.87%) (Table III). Self-gain/other-lost > Self-lost/other-gain 12 Beyer et al [2014a] 40 Self-won/other-lost > Self-lost/other-won 12 Beyer et al [2014b] 41 Self-won/other-lost > Self-lost/other-won 3 Brunnlieb et al [2013] 15 Self-won/other-lost > Self-lost/other-won 25 Cikara et al [2011] 18 Favored team's success/rival team's failure > control 9 Delgado et al [2008] 17 Self-gain/other-lost > Self-lost/other-gain 5 Du et al [2013] 19 Self-won/others-lost > self-lost/others-won 12 Dvash et al [2010] 16 Relative gain > relative loss 6 Emmerling et al [2016] 15 Self-won/other-lost > Self-lost/other-won 9 Fareri and Delgado [2014] 18 Self-won/others-lost > self-lost/others-won: social > non-social 8 Fliessbach et al [2007] 33 Self-won/other-lost > self-lost/other-won 1 self-lost/other-lost 8 Fliessbach et al [2012] 64 Self-won/other-lost > self-lost/other-won 1 self-lost/other-lost 2 Haruno & Frith [2010] 52 Parametric analysis, positive correlation with absoluate differences between two peoeple (self > other) Baumgartner et al [2011] 32 disadvantageous outcomes > equal outcomes 17 Beyer et al [2014a] 40 Self-lost/other-won > Self-won/other-lost 7 Beyer et al [2014b] 41 Self-lost/other-won > Self-won/other-lost 5 Cikara et al [2011] 18 Favored team's failure/rival team's success > control 3 Civai et al [2012] 19 disadvantageous outcomes > equal outcomes 12 Corradi-Dell'Acqua et al [2016] 19 disadvantageous outcomes > equal outcomes 21 Emmerling et al [2016] 15 Self-lost/other-won > Self-won/other-lost 4 Fatfouta et al [2016] 23 disadvantageous outcomes > equal outcomes 18 Farmer et al [2016] 18 disadvantageous outcomes > equal outcomes 6 Feng et al [2016] 40 disadvantageous outcomes > equal outcomes 10 Fliessbach et al [2012] 64 disadvantageous outcomes > equal outcomes 1 Gospic et al [1983] 17 disadvantageous outcomes > equal outcomes 4 Gradin et al [2015] 25 disadvantageous outcomes > equal outcomes 10 Guo et al [2013a] 18 disadvantageous outcomes > equal outcomes 10 Guo et al [2...…”
Section: Primary Ale Meta-analysis Resultsmentioning
confidence: 99%
“…L, left; R, right. Assaf et al [2009] 19 Self-gain/other-lost > Self-lost/other-gain 5.02 Beyer et al [2014a] 40 Self-won/other-lost > Self-lost/other-won 5.19 Beyer et al [2014b] 41 Self-won/other-lost > Self-lost/other-won 6.00 Brunnlieb et al [2013] 15 Self-won/other-lost > Self-lost/other-won 1.86 Cikara et al [2011] 18 Favored team's success/rival team's failure > control 2.08 Delgado et al [2008] 17 Self-gain/other-lost > Self-lost/other-gain 2.10 Du et al [2013] 19 Self-won/others-lost > self-lost/others-won 1.95 Dvash et al [2010] 16 Relative gain > relative loss 6.90 Emmerling et al [2016] 15 Self-won/other-lost > Self-lost/other-won 4.65 Fareri and Delgado [2014] 18 Self-won/others-lost > self-lost/others-won: social > non-social 4.27 Fliessbach et al [2007] 33 Self-won/other-lost > self-lost/other-won 1 self-lost/other-lost 6.43 Fliessbach et al [2012] 64 Self-won/other-lost > self-lost/other-won 1 self-lost/other-lost 6.05 Kr€ amer et al [2007] 15 Self-won/other-lost > Self-lost/other-won 2.95 Kishida et al [2012] 27 parametric analysis, positive correlated with change of self's rank 4.01 Le Bouc and Pessiglione [2013] 32 Parametric analysis, positive correlation with relative income 4.71…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation